The Influence of Family Empowerment with Participatory Rural Appraisal (PRA) Methods on Covid19 Prevention Compliance - Luluk Fauziyah Januarti; Mustofa Haris (Universitas STRADA Indonesia, 2021)
Research design uses Quasy Eksperiment with the Two Group Pre Test – Post Test design approach. The sample was taken by 32 treatment groups and 32 control groups. Sampling technique using Probability sampling with simple random sampling technique. Family empowerment research dependent variables with Participatory Rural Appraisal (PRA) method, Independent Variables of COVID19 prevention compliance. Data collection techniques using questionnaire sheets. Statistical tests using Mann whitney. The results of the study after being given treatment obtained the results of the Mann Whitney p-value 0.012 (p <0.05) so that it can be concluded that there are differences in family empowerment to the compliance of covid-19 health protocols between the two groups